Efeitos de diferentes estratégias não formais na sensibilização de adolescentes para a conservação da biodiversidade: uma associação entre pesquisa científica e extensão universitária - Nunes, Maria Erivanir Rodrigues (2015)
Frequent changes in the biodiversity of the planet, from the anthropic actions, constitutes a major environmental problem for humanity. Thus the development of environmental education (EE) interventions within the primary, indicates be an important strategy for raising awareness of man and to achieve the objectives proposed for the EE. Thus, this study aimed to, use scientific research as a key tool for building knowledge and environmental awareness in the Caatinga. Precisely investigate the following hypotheses: (1) increased knowledge is directly related to increased interest in biodiversity conservation, (2) the presence of practical activities results in a higher degree of assimilation of knowledge and the development of interest in conservation nature and (3) the level of involvement is related to the increase of knowledge and interest in biodiversity conservation. Thus, it constitutes the sample size, 131 students of the second grade of a public school in Rio Grande do Norte state, Brazil. For the implementation of research, these students were divided into groups and classified by the intensity of participation in the research on three levels, low, medium and high. Each group participated in activities with different degree of knowledge, in order to identify the scope and effectiveness of environmental intervention. For this, the data were obtained by means of so-called pre-test questionnaires (applied before the action) and post-test applied to three levels of intensity of participation (low, medium and high) immediately after the intervention actions. The findings showed from the high level of participation, the greater the encouragement and involvement of students in practical activities in natural environments, the greater the increase in knowledge and interest in prioritizing conservation actions. As also demonstrated that disassociated activities of direct participation of students, even favorable environment for education may not have the expected effect, such as increased knowledge and environmental interest, as evidenced by the low level. Thus, it was still possible to identify the association of knowledge and active involvement of students in EE stock is a stimulating learning environment, causing changes in understanding and how to use natural areas as well as providing a better assimilation of knowledge. These aspects contribute to modify the environmental meanings built by the students and arouse the interest and the environmental conservation of desire